Syntheses of the first coordination compounds of the new strong molecular electron donor and double proton sponge 1,4,5,8-tetrakis(tetramethylguanidino)naphthalene - Vitske, Viktoriia; König, Carolin; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
Herein we report on the synthesis and properties of a new electron donor featuring an aromatic system to which four guanidino groups are attached, namely, 1,4,5,8-tetrakis(tetramethylguanidino)naphthalene (ttmgn). The molecule is a double proton sponge with an asymmetric N-H···N bridge being formed in the protonated form. Oxidation is followed electrochemically, and two oxidation waves at E1/2(CH3CN) = -0.25 and +0.50 V vs. SCE are observed. Chemical oxidation with I2 yields ttmgn(I3)2, in which the I3- units interact with the ttmgn2+ cations through I···C contacts. Reaction with an excess amount of Br2 leads to removal of four electrons from the aromatic system and formation of the salt (ttmgn)Br4 with a chair-type conformation of the C10 core. The binuclear Al alkyl complex [(ttmgn)(AlMe2)2][BPh4]2 can be prepared by reaction between the diprotonated ttmgn molecule and AlMe3 and serves as a benchmark system for the understanding of dynamic effects. Magnetic superexchange through the ligand unit is studied for the binuclear CoII complex [(ttmgn)(CoCl2)2]. SQUID measurements show an extremely weak antiferromagnetic coupling. The coupling might be affected by the unusual geometry of the coordination compounds of ttmgn, in which the metal ions are significantly displaced from the plane defined by the aromatic ring of the ttmgn ligand. We also report the analogous Co complex of ttmgb [ttmgb = 1,2,4,5-tetrakis(tetramethylguanidino)benzene], namely, [(ttmgb)(CoCl2)2], in which the bonding situation is quite different.